The Influence of Different Nonsteroidal Anti-Inflammatory Drugs on Alveolar Bone in Rats: An Experimental Study - Mujgan Gungor Hatipoglu; Sermet Inal; Sahin Kabay; Muhammet Kasim Cayci; Ayşenur Deger; Halil Isa Kuru; Sayit Altikat; Gizem Akkas (University of Zagreb. School of Dental Medicine, 2015)
The aim: The aim of this study was to investigate the effect of dexketoprofen trometamol, meloxicam, diclofenac sodium on any untreated alveolar bone when they are used as drugs for another indication. Materials and Methods: Twenty eight male Spraque-Dawley rats were randomized into four groups as dexketoprofen trometamol (Group I), meloxicam (Group II), diclofenac sodium (Group III) and control group. Nonsteroidal anti-inflammatory drugs (NSAID) were administered after a fibula fracture for 10 days. Untreated alveolar bone was histopathologically examined for spongious bone density, osteoclastic density and osteoblastic density. Results: Spongious bone density was lower in study groups (Group I, group II and group III) than the control group (p<0.05). In contrast, the increase in osteoclastic density was observed in other groups apart from the control group (p<0.05). Osteoblastic density was evaluated and it was determined that group II and group III had lower results than the control group (p<0.05) but group I was equal to the control group. Conclusion: This study showed that systemically administrated NSAIDs have the potential to affect untreated alveolar bone. This should also be considered in long term use of NSAIDs.